2004
DOI: 10.1021/ja046804m
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Alkoxy−Oligothiophene Ground and Excited States in Nanochannels

Abstract: Two oligothiophenes, 4,4'-dipentoxy-2,2'-dithiophene and 4,4"-dipentoxy-2,2':5',2":5",2' ''-tetrathiophene, have been included in the nanochannels of the autoassembling host TPP (tris-o-phenylenedioxycyclotriphosphazene). The effect of the confinement on the structure and properties of the two dyes, as conformational arrangements, dynamics, and photophysical behavior, was addressed by the combination of high spinning speed solid-state NMR and time-resolved EPR spectroscopy. We compared the conformations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Such high-field resonances are typical of n-alkane chain-end methyls, experiencing the effect of gauche conformations of the vicinal -CH2-CH2− bond (-gauche effect). [12] Since the trans-to-gauche conversion accounts for = -5 ppm in hydrocarbons, the observed CH3 chemical shifts of about 3 ppm upfield with respect to the expected trans conformation resonance, indicates that at least a 0.5 fraction of gauche conformation is explored, consistent with XRD data. Spin-lattice relaxation times from 0.3 to 1.7 s for Nva alkyl pendant group are close to the theoretical minimum value, indicating an efficient relaxation mechanism of about 10 8 Hz.…”
supporting
confidence: 65%
“…Such high-field resonances are typical of n-alkane chain-end methyls, experiencing the effect of gauche conformations of the vicinal -CH2-CH2− bond (-gauche effect). [12] Since the trans-to-gauche conversion accounts for = -5 ppm in hydrocarbons, the observed CH3 chemical shifts of about 3 ppm upfield with respect to the expected trans conformation resonance, indicates that at least a 0.5 fraction of gauche conformation is explored, consistent with XRD data. Spin-lattice relaxation times from 0.3 to 1.7 s for Nva alkyl pendant group are close to the theoretical minimum value, indicating an efficient relaxation mechanism of about 10 8 Hz.…”
supporting
confidence: 65%
“…The channels accept small molecules eagerly, 22 and detailed dynamic NMR and EPR studies of the motion of oligothiophenes included in TPP inclusion have been reported. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The molecular dynamics of guest molecules are mainly investigated using NMR, because the fast uni-axial rotation or the structural disorder of guest molecules makes the determination of the molecular structure or orientation in the nanochannels by single crystal X-ray diffraction difficult. This is even the case for TPP/benzene IC, in which the shape of guest molecules is simple and highly symmetric [16,17,18,19,20]. In addition, TPP is also a medium for gas storage because the strong affinity of the wall of the nanochannels makes it possible to include even gas molecules [21,22,23].…”
Section: Introductionmentioning
confidence: 99%